2016
DOI: 10.1128/aac.00630-16
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of the Etest and EUCAST Methods for Antifungal Susceptibility Testing of Candida Isolates to Micafungin

Abstract: In vitro susceptibility of 933 Candida isolates, from 16 French hospitals, to micafungin was determined using the Etest in each center. All isolates were then sent to a single center for determination of MICs by the EUCAST reference method. Overall essential agreement between the two tests was 98.5% at ؎2 log 2 dilutions and 90.2% at ؎1 log 2 dilutions. Categorical agreement was 98.2%. The Etest is a valuable alternative to EUCAST for the routine determination of micafungin MICs in medical mycology laboratorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The highest amphotericin B modes were for C. krusei (1 g/ml), A. flavus SC (2 g/ml), and A. terreus SC (4 g/ml) ( Tables 2 and 3). In general, similar Etest data have been previously published (34)(35)(36)(37)(38)(39)(40)(41), but as observed in prior ECV studies, our MIC ranges tended to be wider, especially for Candida spp. versus anidulafungin and micafungin.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The highest amphotericin B modes were for C. krusei (1 g/ml), A. flavus SC (2 g/ml), and A. terreus SC (4 g/ml) ( Tables 2 and 3). In general, similar Etest data have been previously published (34)(35)(36)(37)(38)(39)(40)(41), but as observed in prior ECV studies, our MIC ranges tended to be wider, especially for Candida spp. versus anidulafungin and micafungin.…”
Section: Resultssupporting
confidence: 77%
“…Although BPs are not available for most fungal species-agent combinations, CLSI ECVs have been established for more fungal species (both prevalent and less common) based solely on reference in vitro data (10,11,18). The Etest method has been extensively evaluated for testing both yeasts and molds and the antifungal agents included in the present study (34)(35)(36)(37)(38)(39)(40)(41) to estimate essential and categorical agreement with reference methods or the potential Etest's superior value as a predictor of antifungal resistance. Given that the Etest relies on CLSI BPs for clinical interpretation of results, method-dependent Etest ECVs could be useful in the clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…Espinel-Ingroff et al 34 , reported an essential agreement of 95% and a categorical agreement of 97% between Etest and CLSI BMD method while Marcos-Zambrano et al 35 , reported an essential agreement of 90% and a categorical agreement of >90% between Etest and EUCAST BMD method. Bougnoux et al 36 , in a recent study based on 933 Candida species isolates (including 152 C. glabrata isolates) reported an essential agreement of 98.5% and a categorical agreement of 98.2% between Etest and EUCAST BMD method. Similar to these studies, our data also support that Etest is an easy and reliable method for routine AST of clinical C. glabrata isolates to micafungin.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, high micafungin MIC results have been shown to correlate with the occurrence of FKS mutations, which is also the case for high caspofungin MICs (Pham et al, 2014). We used Etest® for the echinocandin susceptibility testing since it is considered a valuable alternative to the EUCAST broth microdilution method for routine susceptibility testing of micafungin in C. glabrata isolates, with categorical agreement of 96.7% (Bougnoux et al, 2016)…”
Section: Methodsmentioning
confidence: 99%